Training regimen of an elite ultramarathon runner: A case study of what led up to the 24-hour world-record run - Byrne, J.; Lynch, S.; Mokha, G. M. (International Journal of Sports Physiology and Performance, 2024)
Purpose Ultramarathon running has gained popularity over several decades. Although there has been considerable research on training for other running events, from the 100-m to the marathon at 26.2 miles (42.2 km), there is little evidence on best practices for ultramarathons, where distances potentially exceed 100 miles (160.9 km).